ANALISIS PERBANDINGAN TARIF PEMOTONGAN PPH PASAL 21 BERDASARKAN PERATURAN PEMERINTAH NO. 58 TAHUN 2023 DAN TARIF EFEKTIF RATA-RATA TAHUN 2024 (Studi Kasus PT Maheswari Daya Gemilang) - Putri Diana Sari; Miya Dewi Suprihandari (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
The basis for this research is the application of the new regulation on the rate of Income Tax (PPh) 21 through Government Regulation no. 58 of 203 which is the previous regulation, and in 2024 the Indonesian government began implementing a new rule, namely the Average Effective Rate 2024. In this research, a qualitative approach with the type of case study is used. The purpose of this research is to understand the phenomena experienced by the research subject, which is PT Maheswari Daya Gemilang, which is currently facing changes in PPh 21 rates. Not only that, the purpose of this research is to find out the overall how the company manages and implements policy changes in taxation rates. In addition, documentation studies are used to collect data by examining company documents related to the implementation of taxation policies, especially in the application of PPh chapter 21 rates. This research shows that the application of the Average Effective Rate 2024 has a good impact because its application is easier and more efficient because the TER rate system facilitates the calculation of tax calculations to be faster and more accurate.